Avaliação da atividade inseticida de Deltametrina em Triatoma Williami Galvão, Souza e Lima, 1965 - Gomes, Letícia Pinho (2016)
Chagas disease is caused by the protozoan Trypanosoma cruzi, with endemic characteristics is a major public health problem in the Americas. The vector transmission is the main mechanism of human infection and occurs through contact of the parasite in feces or urine vector, with the vertebrate host during or after blood feeding insects of Triatominae. Thus, the importance of the insects is linked to its epidemiological relevance as vectors of the parasite and its vector potential is closely related to their ability to survive in anthropic environment for expanding the possibilities of meeting the parasite to humans. Among the triatomine species present in the region of the middle Araguaia, Triatoma williami specimens has often been found by visiting anthropogenic environments in the municipality of Barra do Garças, MT with infection rates by T. cruzi about 30%, increasing the risk of transmission of the parasite to humans vertebrate hosts. Among the measures that reduce the risk of vector T. cruzi infection the use of pyrethroid insecticides, especially deltamethrin, has been recommended in vector control campaigns since the 1980s. Despite the importance of chemical control, rational use of these compounds is essential to ensure human and environmental health. However, no controlled studies have established the safe use of insecticides in populations of T. williami. Thus, the aim of this study was to know the action of deltamethrin 2.5% on T. williami. For this purpose, they were tested Deltamethrin eight concentrations on first instar nymphs for 24 and 72 hours. Deltamethrin was not introduced effective residual effect for T. williami with exposure time of 24 hours of nymphs to pyrethroid, already with 72 hours contact demonstrated effect 120 days after the chemical treatment. Through this work it was possible to note that deltamethrin has lethal effect on T. williami, however, it requires a long period of exposure as a guarantee of its effectiveness.